Atributos de qualidade de frutos de tangerineira 'Poncã' adubada com composto orgânico, em dois ciclos agrícolas de avaliação - Ramos, Dayana Portes [UNESP] (2014)
The purpose of the research was to evaluate the effects of organic matter levels on fruit quality of 'Poncã' mandarin (Citrus reticulata, Blanco). The research was conducted in Experimental Farm of the Faculdade de Ciências Agronômicas/ UNESP, located in São Manuel city, São Paulo State, Brazil. The treatments consisted of levels at 50, 100, 150 and 200% of nitrogen present in organic matter, more on witness treatment. The experimental design was entirely randomized with five treatments, four replications and tree plants per plot. It was employed the analysis of regression in each evaluation period, corresponding of the 2009/2010 and 2010/2011 crop cycles. The physico-chemical properties of fruits were evaluated: weight (g), fruit equatorial diameter (cm), juice yield (%), technological index (kg SS.box-1 ), solid soluble (ºBrix), titratable acidity (%), "ratio" and ascorbic acid (mg.100 ml-1 juice). The results showed that the technological index and soluble solids decreased as was increased rates of organic compost.